Mesoscopic superstructures of flexible porous coordination polymers synthesized via coordination replication1. Issue 10 (14th October 2015) - Sumida, Kenji; Moitra, Nirmalya; Reboul, Julien; Fukumoto, Shotaro; Nakanishi, Kazuki; Kanamori, Kazuyoshi; Furukawa, Shuhei; Kitagawa, Susumu
<x xml:space="preserve">Abstract</x> Monolithic superstructures of two- and three-dimensional flexible frameworks are prepared via coordination replication from a copper hydroxide parent phase.